A new iron supplement: The chelate of pig skin collagen peptide and Fe2+ can treat iron-deficiency anemia by modulating intestinal flora - Jiang, Shan; Dong, Weichao; Zhang, Zhen; Xu, Jing; Li, Haoran; Zhang, Jiayu; Dai, Long; Wang, Shaoping (Frontiers in Nutrition, 2022)
Introduction Iron deficiency anemia (IDA) is one of the most common nutritional diseases encountered all over the world. Nowadays, oral iron supplementation is still the mainstay of IDA treatment. Methods In this study, a new iron nutritional supplement named pig skin collagen peptides ferrous chelates (PSCP-Fe) was prepared, and its structure was characterized by the scanning electron microscopy, sykam amino acid analyzer and Fourier transform infrared spectroscopy (FTIR). The anti-IDA activity of PSCP-Fe was evaluated in low-Fe2+ diet-induced IDA in rats. 16S amplicon sequencing technology was then used to reveal the mechanism of PSCP-Fe against IDA. Results The results of amino acid analysis and FTIR showed that aspartic acid (Asp), arginine (Arg), histidine (His), glutamic acid (Glu), cystine (Cys), and lysine (Lys) residued in PSCP chelated readily with Fe2+ through their functional groups. PSCP-Fe treated reversed the hematology-related indexes, such as red blood cells (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentrate (MCHC), serum ferritin (SF), serum hepcidin (HEPC) and serum transferrin receptor (TFR). And its regulatory action was better than that of FeSO4. Moreover, PSCP-Fe alleviated the hepatocyte apoptosis and necrosis, Fe2+ loss, and injury in IDA rats. In addition, PSCP-Fe could significantly retrace the disturbed profile of gut microbiota in IDA rats (p < 0.05) and significantly up-regulated the relative abundances of nine bacterial genus, including Lactobacillus, Alloprevotella, unclassified_of_Oscillospiraceae, and NK4A214_group (p < 0.05). It could also downgrade the relative abundances of Subdoligranulum and Coriobacteriaceae_UCG-002 (p < 0.05). The results of Spearman’s correlation analysis and distance-based redundancy analysis (db-RDA) revealed that Subdoligranulum and Christensenellaceae_R-7_group may be potential microbial markers for effective PSCP-Fe action in the treatment of IDA. Discussion Overall, our results elucidate the interactions between gut bacteria and related cytokines and reveal the mechanisms underlying the anti-IDA effect of PSCP-Fe. They will thus provide a theoretical foundation for PSCP-Fe as a new iron nutritional supplement.